HAK UPAH PEKERJA PKWTT TERHADAP PEMUTUSAN HUBUNGAN KERJA SEPIHAK OLEH PERUSAHAAN PERSPEKTIF UU NO. 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (STUDI KASUS: PUTUSAN PENGADILAN NEGERI JAKARTA PUSAT NOMOR: 134/PDT.SUS-PHI.G/2019/PN.JKT.PST) - Alvin Faizal Adhiaza; Gunardi Lie (Fakultas Hukum Universitas Tarumanagara, 2022)
Termination of Employment Relations often creates experiences between employers andworkers/labourers. Disputes tend to occur between workers/ laborers and employers regarding theemployment relationship. sometimes workers/laborers pay attention to the labor rules in Law Number13 of 2003 concerning Manpower, in that provision already regulates the rights and obligations of theparties, as well as regulates industrial cooperation agreements. Therefore, this study aims to find outhow the company's considerations and responsibilities regarding payment of industrial responsibilitypayments in the Central Jakarta District Court Decision Number:134/Pdt.Sus-PHI.G/2019/PN.JKT.PST. The research method used is normative legal research with aprescriptive nature of research, and uses primary legal materials, secondary legal materials, and usesa statutory approach. The researcher obtained the results, that the consideration is in accordance withLaw Number 2 of 2004 concerning Settlement of Industrial Relations Disputes, employers are requiredto pay compensation money, but it is not in accordance with the Manpower Law on refusal of wages.Workers also do not get their rights such as employment relationship status, wages below theminimum, and employment social security.